2014
DOI: 10.1364/ol.39.002603
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dispersive and saturable gain/loss on bistability of nonlinear parity–time Bragg gratings

Abstract: Received Month X, XXXX; revised Month X, XXXX; accepted Month X, XXXX; posted Month X, XXXX (Doc. ID XXXXX); published Month X, XXXX We report on the impact of realistic gain and loss models on the bistable operation of nonlinear parity-time Bragg gratings. In our model we include both dispersive and saturable gain and show that levels of gain/loss saturation can have significant impact on the bistable operation of a nonlinear PT Bragg grating based on GaAs material. The hysteresis of the nonlinear PT Bragg gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 25 publications
1
35
1
Order By: Relevance
“…We describe propagation of light in the time domain using the Maxwell-Bloch equations and taking into account loss and gain saturation. The influence of the saturable nonlinearity on nonreciprocity and bistability of PT -symmetric structures was previously reported both for transverse [33] and longitudinal geometries [34][35][36][37]. However, those investigations introduced the saturation phenomenologically via the permittivity.…”
Section: Introductionmentioning
confidence: 92%
“…We describe propagation of light in the time domain using the Maxwell-Bloch equations and taking into account loss and gain saturation. The influence of the saturable nonlinearity on nonreciprocity and bistability of PT -symmetric structures was previously reported both for transverse [33] and longitudinal geometries [34][35][36][37]. However, those investigations introduced the saturation phenomenologically via the permittivity.…”
Section: Introductionmentioning
confidence: 92%
“…As the intensity is increased, the phase grating is formed. This structure differs from one in (Phang et al 2014) where the phase grating is constant and only the positive Kerr nonlinearity is introduced throughout the grating.…”
Section: Introductionmentioning
confidence: 97%
“…The impact of Kerr-nonlinearity has also been analysed in the frequency domain in (Achilleos et al 2012;Lin et al 2011;Musslimani et al 2008;Ramezani et al 2010) assuming a non-saturable and frequency independent gain/loss material. In our recent paper we have analysed nonlinear PT Bragg gratings in time domain and have demonstrated that gain/loss saturation preserve the hysteresis properties of nonlinear PT Bragg grating, and that in the absence of gain/loss saturation hysteresis vanished (Phang et al 2014). It is important to note that PT Bragg gratings (PTBG) have different diffraction properties depending on the side of excitation in that the transmittance is the same regardless of the side of excitations but reflectances are different.…”
Section: Introductionmentioning
confidence: 99%
“…In lossless structures the eigenfrequencies below the threshold point are purely real, whilst above the threshold point they become complex conjugates indicating the presence of both gain and loss modes. PT symmetric structures based on Bragg gratings, coupled waveguides and cavities have been investigated both theoretically and experimentally, and have demonstrated unidirectional loss-induced invisibility, simultaneous lasing and coherent-absorption and, recently, a loss-induced lasing mode [5][6][7][8]. Different applications have been proposed exploiting the behavior at the threshold point, such as optical switching, an optical logical-gate, lasing and memory devices.…”
Section: Introductionmentioning
confidence: 99%